Socio-psychological factors of academic procrastination in students - Mardiyeva Shakhnoza Amirovna (Global Scientific Publishing, 2025)
This article analyzes the social and psychological factors of academic procrastination among students. The results of the research reveal the importance of determinants such as motivation, self-esteem, time management, social influences, and emotional regulation
Keywords: Academic procrastination; social determinants; emotional regulation